Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1068/a35150
|View full text |Cite
|
Sign up to set email alerts
|

Deprivation, Diet, and Food-Retail Access: Findings from the Leeds ‘Food Deserts' Study

Abstract: Abstract. Within a context of public policy debate in the United Kingdom on social exclusion, health inequalities, and food poverty, the metaphor of the`food desert' caught the imagination of those involved in policy development. Drawing from a major cross-disciplinary investigation of food access and food poverty in British cities, the authors report in this paper findings from the first`before/after' study of food consumption in a highly deprived area of a British city experiencing a sudden and significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
308
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(337 citation statements)
references
References 31 publications
(30 reference statements)
21
308
0
3
Order By: Relevance
“…[30][31][32][33][34] One study in particular, using an experimental design, found that individuals who previously consumed few fruits and vegetables significantly increased their consumption after a new supermarket was built in their neighborhood. 35 These studies underscore the possibility that the association between supermarket access and obesity found in our analysis, as well as in earlier studies, may be predominately mediated by dietary consumption. Individuals with greater access to supermarkets may consume a greater variety of healthy foods thus promoting healthier body weight.…”
Section: Discussionsupporting
confidence: 86%
“…[30][31][32][33][34] One study in particular, using an experimental design, found that individuals who previously consumed few fruits and vegetables significantly increased their consumption after a new supermarket was built in their neighborhood. 35 These studies underscore the possibility that the association between supermarket access and obesity found in our analysis, as well as in earlier studies, may be predominately mediated by dietary consumption. Individuals with greater access to supermarkets may consume a greater variety of healthy foods thus promoting healthier body weight.…”
Section: Discussionsupporting
confidence: 86%
“…In such localities, consumers are highly dependent on convenience stores as they often provide the only remaining access to grocery stores, with the consequence that consumers in these areas tend to pay higher prices and have a more restricted diet (Whelan et al 2002). At the other extreme, a handful of major studies have explored the effect of provision interventions from the opening of major multiple-owned superstores in food deserts in Leeds (Wrigley et al 2002a;Wrigley et al 2003;Wrigley et al 2002b) and Glasgow (Cummins et al 2008), attempting to assess the effects on diet. These findings provide contrary evidence that such large-scale initiatives have a positive effect on the dietary patterns of local households.…”
Section: Enhancing Consumer Choice and Accessmentioning
confidence: 99%
“…This involved an uncontrolled before-and-after 'intervention' (the intervention being a new Tesco superstore) study of changes in food consumption patterns in a highly deprived area. Wrigley et al (2002bWrigley et al ( , 2003 concluded that there were significant improvements post-intervention in terms of food retail access, accompanied by improved diet amongst some groups of…”
Section: A) Retail-led Regeneration and Food Desertsmentioning
confidence: 99%
“…Purchase of these products can be considered from the data collected. For example, Wrigley et al, (2002bWrigley et al, ( , 2003 investigated the way that shoppers switched their store for the purchase of fruit and vegetables. The Seacroft study suggested that whilst shoppers switched away from limited line discounters for their fruit and vegetable purchasing those who patronised smaller shops for fruit and vegetable purchasing were less likely to switch.…”
Section: D) Store Patronage and Fruit And Vegetable Consumptionmentioning
confidence: 99%
See 1 more Smart Citation